2013
DOI: 10.1007/s10461-013-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Reported Physical and Sexual Abuse in Childhood and Adult HIV Risk Behaviour in Three African Countries: Findings from Project Accept (HPTN-043)

Abstract: Childhood sexual and physical abuse have been linked to adolescent and adult risky sexual behaviors, including early sexual debut, an increased number of sexual partners, unprotected sex, alcohol and drug use during sex and sexual violence. This paper explores these relationships among both men and women who report histories of childhood abuse from representative samples of communities in three countries in southern and eastern Africa (South Africa, Zimbabwe and Tanzania). Data were collected as part of a 3-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 49 publications
8
76
4
5
Order By: Relevance
“…Experiences of violence in childhood are a known risk factor for later revictimization, including IPV [34,35]. The risk of IPV increases through witnessing violence against a mother [36], and experiencing sexual violence in childhood [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences of violence in childhood are a known risk factor for later revictimization, including IPV [34,35]. The risk of IPV increases through witnessing violence against a mother [36], and experiencing sexual violence in childhood [11].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of IPV increases through witnessing violence against a mother [36], and experiencing sexual violence in childhood [11]. A 2013 study found a three-fold increase in gender-based violence among women who had experienced childhood violence [35]. Globally, evidence has also shown levels of childhood sexual abuse among FSWs to range from 32.4%–42.0%, and that sexual abuse in childhood is higher among SWs than other women [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Previous scholars documented that when teenage girls lack support and encouragement from society to claim their sexual identity as part of their human rights; they feel marginalized and expose themselves to risky sexual behaviours (Koen, 2009;Van Eijk, 2007). Risk sexual behaviour includes being sexually active, having multiple sexual partners, practicing unsafe sex, sex while drunk, usage of drugs, sexual promiscuity and sexual or partner violence (Dunkle, Jewkes, Nduna, Levin, Jama, Khuzwayo, Koss & Duvvury, 2006;Richter, Komárek, Desmond, Celentano, Morin, Sweat & Coates, 2013). Due to stress, to cover their emotional inadequacy, they develop a tendency to drink alcohol, sleep with multiple sexual partners and feel the need to prove that they are able to have children before marriage as a way of attaining adult status (Gustafsson & Worku, 2002;Jewkes et al, 2009) which impairs their psychological wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…The loveLife NGO primarily addresses HIV prevention among youth, and tis work intersects with child violence issues because of its focus on broader social determinants of risk. Research shows, for example, that childhood sexual and physical abuse contributes to later, HIV-transmission-causing sexual risk behaviour and victimisation through early sexual initiation, unprotected sex, and use of alcohol and drugs during sexual activity (Richter et al, 2014 While not extensive, there have been some evaluations of the effectiveness of Soul City's C4D efforts, with evidence found of positive attitude change regarding the acceptability of violence (Soul City Institute, n.d., 2011). Soul City deploys a variety of measurement methods, including quantitative baseline and follow-up surveys, and some qualitative data (Soul City Institute, 2016).…”
Section: A Social Ecology Of Causal Factors For Violence Against Chilmentioning
confidence: 99%